External Dacryocystorhinostomy and Patient Satisfaction: Perspective of General Ophthalmologist - Rasaily, Suresh BK; Pokharel, Kaushal; Katuwal, Sulaxmi; Bishowkarma, Sabita; Limbu, Ben; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2021)
Introduction: This study aimed to evaluate patient satisfaction over time in patients undergoing external dacryocystorhinostomy for primary nasolacrimal duct obstruction when done by a general ophthalmologist. Materials and methods: This prospective interventional case series was done in a secondary level eye hospital in the Midwestern region of Nepal from 1st January 2018 to 30th December 2018. Fifty-four consecutive adult patients diagnosed with primary nasolacrimal duct obstruction who underwent external dacryocystorhinostomy performed by a general ophthalmologist were included. The surgical success rate was determined at six months on the basis of the resolution of symptoms with patency on syringing. Postoperative patient satisfaction was evaluated 6 months after surgery with a standardized Glasgow Benefit Inventory and post-intervention questionnaire. Results: A total of 54 eyes were operated on within the study period and a larger number of surgeries were done in the age group 26-30 years. Female constituted 79.6 % and male 20.4% with a ratio of 3.9:1. Overall surgical success rate 6 months after surgery was 96.30%. The mean total Glasgow benefit inventory (GBI) score was 48.83 ± 23.87 (95% CI, 42.96- 56.95), mean general subscale score was 52.70± 23.28 (95% CI, 46.49-60.38), social support subscale was 49.69 ± 44.68 (95% CI, 41.15-60.35) and physical health subscale score was 37.07 ± 41.19 (95% CI, 27.48-49.26). Conclusion: The external dacryocystorhinostomy surgeries performed by general ophthalmologists achieved an excellent surgical success rate and good patient satisfaction proven by a validated questionnaire.